The 'Great' Shoe question: Tradition,Legitimacy and Power in Colonial India - K.N. Panikkar (Studies in History 1998; 14; 21, 1998)
The selective appropriation of traditional cultural practices was a part of the technology of British colonial control in India. The incorporation of indigenous mores helped to invest colonial rule with an illusion of continuity and legitimacy. Since appropriation tended to impart new meanings and symbolic importance to existing practices, tradition became a site of contest. Through the debate on what constituted the authentic tradition of the 'natives', several issues germaine to the question of subjection and resistance were articulated and negotiated. This essay is an attempt to explore these issues in the context of the shoe regulation of 1854 and the controversies that it entailed.